Critical Success Factors of Renovation Projects - Juneja, Ashish; Dubey, Atul (International Journal of Scientific Research in Civil Engineering, 2018)
Today it is our duty to promote sustainable development in construction industry.This will help us to encourage the growth of Real estate sector, which includes residential,commercial,industrial, infrastructure amenities. There are many ways to promote sustainable development in construction like using waste material, maintenance, replacement and renovation of existing structures. Among all ways, we have chosen renovation for our research work. Renovation of existing infrastructure helps our society by reducing cost of construction,genarating new employments and it also helps us to deal in recession period when the rate of new construction works are low.The future of real estate industry in developed or developing country is to provide reconstruction, renovation or retrofitting of old buildings which may have been damaged by atmospheric action, earthquake, tsunami, flood etc and due to overloading settlement occurs in structure.Nowdays in our country Govt declared smart city project in different different cities like amritsar, indore etc so renovation is the best way to make city smart at low cost which ultimately genrate employment.In this research we will study the renovation projects and factors affecting renovation work.The word “CSF” used in this reseach is related to those factor which actually comes during renoavtion work and these factors are called critical success factors.Analysis of this research provides precise and concise finding on actual scenario happening in india on renovation work.The method adopted for this research is quitionnaire survey and 45 respondent are selected for research.and for analysis of respondent reponses we have used SPSS software.